POSSIBILITIES FOR ASSESSING THE EFFECTIVENESS OF TREATMENT OF ATOPIC DERMATITIS BASED ON ANALYSIS OF COLOR CHARACTERISTICS OF VIDEO DERMATOSCOPIC IMAGES - Oleh Avrunin; Alexey Trubitcin; Olga Isaeva; Viktoriia Klymenko (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of the article is the study of the color characteristics of video dermatoscopic images of affected skin areas of children with atopic dermatitis and the development of an automated diagnostic system for processing and analysis of dermatoscopic images. The aim of the work is to develop an objective method for assessing the skin condition of children with atopic dermatitis based on numerical analysis of images of affected skin areas. The objectives of the work were to collect a life history of children with atopic dermatitis, study the color characteristics of video dermatoscopic images of affected skin areas and further develop an automated diagnostic system for processing and analyzing dermatoscopic information. Research Methods. During the diagnostic examinations of children with atopic dermatitis, a history of life was collected and the initial dermatological status of patients was described. A comprehensive assessment of the severity of the disease was performed using the SCORAD index. Image registration was carried out using a UM039 digital video dermatoscope with optical magnification up to 200 times, resolution of the receiving matrix 2880 × 1800 image elements, equipped with a built-in block of adjustable LED lighting, a tripod and a rotary 3-inch display. The images were captured on a microSD card with subsequent transfer of data to the database on the computer. The results of the study, based on the data obtained, allowed us to assess the intensity and dynamics of the inflammatory processes of the affected areas of the skin of children with atopic dermatitis and to formulate the principles of the automated diagnostic system for processing and analysis of dermatoscopic images. Conclusion. At the end of the study, the authors conclude that to monitor the skin condition in the treatment of atopic dermatitis, the analysis of the color components of the affected areas on the HSV scale can be used, which allows the specialist to intuitively observe the results of the therapy in a natural color space for human perception. As prospects for the development of the work, the authors substantiate the prerequisites for the development of a complete automated system for the comprehensive diagnosis of atopic dermatitis and its clinical trial. Such a system can make it possible to form a preliminary diagnosis and determine the severity of the disease based on the evaluation of color channels of images of affected skin areas and additional diagnostic data.